2017
DOI: 10.1186/s13071-017-2107-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of socio-demographic characteristics and household water management on Aedes aegypti production in suburban and rural villages in Laos and Thailand

Abstract: BackgroundDengue fever is a mosquito-borne disease accounting for 50–100 million annual cases globally. Laos and Thailand are countries in south-east Asia where the disease is endemic in both urban and rural areas. Household water storage containers, which are favourable breeding sites for dengue mosquitoes, are common in these areas, due to intermittent or limited access to water supply. This study assessed the effect of household water management and socio-demographic risk factors on Aedes aegypti infestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 40 publications
9
23
1
11
Order By: Relevance
“…Previous studies reported that washing containers with a brush or sponge to remove mosquito eggs was effective for dengue control [9,17,22,[24][25][26]; however, this study did not find that relationship. This might be because some water containers were large and therefore difficult to wash, especially those that were rectangular, cement, and built in the bathroom corner.…”
Section: Discussioncontrasting
confidence: 88%
“…Previous studies reported that washing containers with a brush or sponge to remove mosquito eggs was effective for dengue control [9,17,22,[24][25][26]; however, this study did not find that relationship. This might be because some water containers were large and therefore difficult to wash, especially those that were rectangular, cement, and built in the bathroom corner.…”
Section: Discussioncontrasting
confidence: 88%
“…Rainfall can affect the availability of mosquito larval habitats [34]. During rainy and dry periods of the year, permanent water containers are common in and around households; some located in toilet or bathroom spaces providing continuous year round mosquito production [35–39, 64]. Large water storage jars and tanks are the most commonly used containers in Thailand [64].…”
Section: Discussionmentioning
confidence: 99%
“…During rainy and dry periods of the year, permanent water containers are common in and around households; some located in toilet or bathroom spaces providing continuous year round mosquito production [35–39, 64]. Large water storage jars and tanks are the most commonly used containers in Thailand [64]. A study correlating rainfall and clinical dengue cases in Thailand from 2002 to 2003 also found that the dengue incidence was closely related with rainfall [65].…”
Section: Discussionmentioning
confidence: 99%
“…( 22 ) Variables used in the SES ranking have been described elsewhere. ( 23 ) Two entomological indices derived from the entomological survey, pupae per household and pupae per person (number of pupae divided by number of persons in each house) were used as potential risk factors for DLI. ( 24 ) National surveillance system data on dengue incidences in both countries were compared with the DLI data obtained in this study.…”
Section: Methodsmentioning
confidence: 99%